CAD-Based Automated Design of FEA-Ready Cutting Tools - Tzotzis, Anastasios; García-Hernández, César; Huertas-Talón, José-Luis; Kyratsis, Panagiotis (Journal of Manufacturing and Materials Processing, 2020)
The resources of modern Finite Element Analysis (FEA) software provide engineers with powerful mechanisms that can be used to investigate numerous machining processes with satisfying results. Nevertheless, the success of a simulation, especially in three dimensions, relies heavily on the accuracy of the cutting tool models that are implemented in the analyses. With this in mind, the present paper presents an application developed via Computer-Aided Design (CAD) programming that enables the automated design of accurate cutting tool models that can be used in 3D turning simulations. The presented application was developed with the aid of the programming resources of a commercially available CAD system. Moreover, the parametric design methodology was employed in order to design the tools according to the appropriate standards. Concluding, a sample tool model was tested by performing a number of machining simulations based on typical cutting parameters. The yielded results were then compared to experimental values of the generated machining force components for validation. The findings of the study prove the functionality of the tool models since a high level of agreement occurred between the acquired numerical results and the experimental ones.